Thirty-Day Readmission Rate Among Patients With Hypertensive Crisis: A Nationwide Analysis. (23rd July 2022) - Ashraf, Muddasir; Zlochiver, Viviana; Bolton, Alexander; Allaqaband, Suhail Q; Bajwa, Tanvir; Jan, M Fuad
Abstract: BACKGROUND: Hypertensive crisis is a life-threatening condition, further classified as hypertensive emergency and hypertensive urgency based on the presence or absence of acute or progressive end-organ damage, respectively. Readmissions in hypertensive emergency have been studied before. We aimed to analyze 30-day readmissions using recent data and more specific ICD-10-CM coding in patients with hypertensive crisis. METHODS: In a retrospective study using the National Readmission Database 2018, we collected data on 129, 239 patients admitted with the principal diagnosis of hypertensive crisis. The primary outcome was the all-cause 30-day readmission rate. Secondary outcomes were common causes of readmission, in-hospital mortality, resource utilization, and independent predictors of readmission. We also compared outcomes between patients with hypertensive urgency and hypertensive emergency. RESULTS: Among 128, 942 patients discharged alive, 13, 768 (10.68%) were readmitted within 30 days; the most common cause of readmission was hypertensive crisis (19%). In-hospital mortality for readmissions (1.5%) was higher than for index admissions (0.2%, P < 0.01). Mean length of stay for readmissions was 4.5 days. The mean hospital cost associated with readmissions was $10, 950, and total hospital costs were $151 million. Age <65 years and female sex were independent predictors of higher readmission rates. Subgroup analysis revealed a higher readmission rate for hypertensive emergency than hypertensive urgency (11.7% vs. 10%, P < 0.01). CONCLUSIONS: All-cause 30-day readmission rates are high in patients admitted with hypertensive crisis, especially patients with hypertensive emergency. Higher in-hospital mortality and resource utilization are associated with readmission in these patients. Graphical Abstract: